A Randomized Control Trial for conservative management of parotid abscess in children - Basnet, Meenakshi; Bedajit, Rajkumar; Neupane, Bijay; Ghimire, Bibek (Journal of Nobel Medical College, 2018)
Background: The optimal conservative treatment protocol of parotid abscess in children is evaluated. Material and Methods: This is a randomized, prospective, cross-sectional study conducted between November 2013 and June 2017 in Nobel Medical College and Teaching Hospital. Thirty children (below 14 years age) suffering from parotid abscess diagnosed by ultrasonography were included in this study. Recurrent parotid abscess cases were excluded. The children were divided into 2 groups by computer assisted randomization into15 patients each. Group A were treated with intravenous Clindamycin while group B were given intravenous Ampicilin + Cloxacillin combination. Results: Five patients of group B did not respond to treatment and were then put on intravenous Clindamycin. Three of these patients responded to treatment but 2 developed multi-lobulated fluctuation and required incision + drainage. Remaining 10 patients in group B and all patients in Group A responded to medical treatment without recurrence. Five patients in group B developed severe diarrhea during antibiotic treatment but none of the patients in group A had this complaint. No patient developed any complications like parapharyngeal abscess or septicemia. Conclusion: Parotid abscess in children can be managed conservatively with intravenous Clindamycin without the need for incision and drainage. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 56-59